Panelist Number IV - Donham, Richard (Academy of Management Journal, 1958)
Focuses on the popularity of executive development programs in universities in the United States. Several universities that have started the programs since 1946; Several companies and business groups that have turned to the universities to organize and teach in live-in programs that are general rather than technical in nature.